BRAF-mutant colorectal cancer, a different breed evolving. (3rd June 2018) - Lai, Eleonora; Pretta, Andrea; Impera, Valentino; Mariani, Stefano; Giampieri, Riccardo; Casula, Laura; Pusceddu, Valeria; Coni, Pierpaolo; Fanni, Daniela; Puzzoni, Marco; Demurtas, Laura; Ziranu, Pina; et al.
ABSTRACT: Introduction : BRAF mutant colorectal cancer (BRAF MT CRC) is a unique category of colorectal tumour with peculiar molecular, pathological and clinical features and poor prognosis; despite recent research, BRAF mutation predictive value and standard treatment of BRAF MT CRC still have to be defined. In this review, we focused on this challenging topic. Areas covered : The potential use of BRAF mutational status among recent additional prognostic and predictive indicators and current treatment strategy in use in these patients is discussed. Moreover, implications and characteristics of new BRAF mutations other than BRAFV600E are analyzed. An in-deep outlook on the immediate future for clinical and translational research in this subgroup of patients is also presented, such as combination therapy with agents targeting the RAS/RAF/MEK/ERK pathway and standard chemotherapy in order to overcome resistance. We performed a research on Pubmed typing 'BRAF mutation', 'colorectal cancer', 'predictive and prognostic value', 'targeted therapy', 'BRAF inhibition'. Expert commentary : BRAFV600E mutation represents a strong, independent negative prognostic factor in II-III stage MSS CRC and mCRC. The best treatment still has to be identified; currently, in good performance status patients, an intensive-chemotherapy-combination remains the standard of care. Further investigations are warranted to explore new horizons to change BRAF MT mCRC outcomes.